1996
DOI: 10.1007/bf01979441
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, melting and spherulitic structure of Β-nucleated random propylene copolymers

Abstract: The characteristics of crystallization, melting and spherulitie growth of a random propylene eopolymer (PRC) containing small amount of ethylene were studied in the presence of a selective 13-nucleating agent (calcium pimelate). It was established that the products of isothermal and non-isothermal crystallization are very rich in 13-modification but have mixed polymorphic composition. The formation of ct-modifieation may be attributed to 13or-transition on the surface of growing ~-spherulites resulting in cx~-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 13 publications
4
49
0
Order By: Relevance
“…for the given random copolymer and even no crossover temperature T (!#) was found below which G ! would be higher than G # [21]. Further studies show that the T (!#) of random copolymer PP shifts to lower temperatures [23].…”
Section: Crystalline Characteristicsmentioning
confidence: 84%
See 2 more Smart Citations
“…for the given random copolymer and even no crossover temperature T (!#) was found below which G ! would be higher than G # [21]. Further studies show that the T (!#) of random copolymer PP shifts to lower temperatures [23].…”
Section: Crystalline Characteristicsmentioning
confidence: 84%
“…Evidently, the rate of crystal growth of PPR increases with the addition of nano-CaCO 3 , but decreases with the addition of !-nucleating agent or !-nucleating agent/nanoCaCO 3 . So far as we know, for the given random copolymer in a wide temperature range, growth rate of !-phase crystal is lower than that of #-phase [15,21,23]. Therefore, the decrease of crystal growth rate of !-nucleating agent/PPR might be caused by generation of !-phase crystal.…”
Section: Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…From the literature it is known that only negligible amounts of the "-phase forms in random (ethylene/ propylene) copolymers with low (1.8-2.5%) ethylene content [12]. Based on these observations, it was suggested that the tendency to "-crystallization is suppressed by the disturbance of the chain regularity [13,34].…”
Section: Polymorphism and Chain Architecture (!-Phase)mentioning
confidence: 99%
“…mediocre toughness, can in principle be improved by increasing the amount of the "-polymorph. Varga and Schulek-Tóth [12] found that the formation of the "-phase was strongly restricted in copolymers of propylene and ethylene. Growth rates of the "-phase in these copolymers were found to be lower for all temperatures studied [13] as compared to pure homopolymers.…”
mentioning
confidence: 99%